Analisis Peranan Pemerintah Daerah Dalam Mendukung Industri UMKM UD. Salacca - Rambe, Jelita Handayani; Ritonga, Meilinda; Lestari, Dini (Yayasan Pendidikan Islam Akmalia, 2022)
One of the UMKM in South Tapanuli is UD. Salacca is a small and medium-sized industry that processes salak fruit into various food and beverage products. The existence of this business provides added value to salak commodities and can be a source of income for business actors. In order to develop the MSME sector, local governments are required to provide facilities, guidance, empowerment and assistance to develop and improve the competitiveness of MSMEs. The purpose of this study is to find out how big the role of the South Tapanuli Regency Government is in supporting Regional MSMEs, especially UD Salacca. The research method used is descriptive qualitative which aims to describe the function of local government participation in the empowerment of UD Salacca MSMEs in Padang Sidempuan City with literature studies or literature reviews and interviews as a source of data for this research. The results obtained from this research are that there are 3 roles carried out by the Regional Government of South Tapanuli Regency in supporting UD Salacca MSMEs, namely: facilitative role, educational role and technical role. The role of the Local Government that has a significant impact on the sale of UD Salacca is by promoting and providing facilities in the form of vacuum frying. In addition, the local government also provides business skills training to help increase the productivity of business results.